Avoidance and Correction of Deformities in Body Contouring - Ferry, Andrew M.; Chamata, Edward; Dibbs, Rami P.; Rappaport, Norman H. (Seminars in Plastic Surgery, 2021)
Body contouring procedures are highly impactful because of their potential to improve a patient's quality of life. These procedures, particularly when performed on patients following massive weight loss, may require secondary intervention to treat residual contour abnormalities. Presently, there is a paucity of information in the literature detailing the avoidance and correction of body contouring deformities. Herein, we will discuss the management of patients seeking revisional body contouring procedures.
Keywords: plastic surgery; body contouring; surgical revision; abdominoplasty; aesthetics